Bargaining with Venture Capitalists: When Should Entrepreneurs Show their Financial Muscle? - Renucci, Antoine (Review of Finance, 2014)
Abstract In this article, I model bargaining between an entrepreneur and a venture capitalist over the profits from an investment project. I show that, conditional on venture capital being available, more personal wealth, even if it is not invested in the project, helps the entrepreneur capture a larger fraction of the profits. I also show that access to bank financing can preclude access to venture capital. This occurs when bank financing works as a lever that raises the fraction of the profits the entrepreneur demands up to a level that is not incentive compatible with initiative from the venture capitalist.